2017
DOI: 10.5751/ace-01118-120216
|View full text |Cite
|
Sign up to set email alerts
|

Variability in egg size and population declines of Herring Gulls in relation to fisheries and climate conditions

Abstract: ABSTRACT. Changes in clutch and egg size in many avian species have been linked to seasonal variation, female physiological state, and laying date during breeding season. These reproductive variables have also been linked to population status and habitat variables. Recent declines in Herring Gull (Larus argentatus) populations in the Atlantic region may be associated with environmental changes, fishery activities, or natural species interactions and fluctuations. We studied variability and trends in Herring Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Declines in Herring Gull abundance have been observed at colonies across Atlantic Canada and the northeastern United States [14, 15]. These declines have been correlated with decreases in fisheries discards due to the collapse of groundfish fisheries and reduced forage fish availability [16, 17], however this is most likely to influence abundance through effects on chick survival rather than adult survival [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Declines in Herring Gull abundance have been observed at colonies across Atlantic Canada and the northeastern United States [14, 15]. These declines have been correlated with decreases in fisheries discards due to the collapse of groundfish fisheries and reduced forage fish availability [16, 17], however this is most likely to influence abundance through effects on chick survival rather than adult survival [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found that the historically sampled eggs (sampled between 1893 and 1984 from across Australia), were significantly larger than those sampled from a single contemporary population in western New South Wales, which were 8% smaller. This size difference may reflect ecologically determined temporal or spatial variation (Barrett et al , Bennett et al ), and it would be interesting to explore differences across additional contemporary populations. An intriguing alternative possibility is that egg volume may have recently declined with a changing climate (Skwarska et al ), in line with climate‐related plasticity in body size in this species (Andrew et al ), and changes over the past century observed in the body size of other species in Australia (Gardner et al ), and worldwide (Møller et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that gull presence is an active influence upon where storm-petrels dig their nest burrows but has little effect on the overall number of storm-petrels nesting in any given area. Recent findings show that the population of Herring Gulls on Kent Island has decreased by 36% since 2001 (Bennett et al 2017) and a decrease in predation pressure might have occurred as a result. Declines in prey availability have resulted in increased predatory efforts toward smaller seabird species and decreased breeding success in gulls (Regehr andMontevecchi 1997, Stenhouse andMontevecchi 1999).…”
Section: Influence Of Predation On Nest Site Usementioning
confidence: 99%
“…Declines in prey availability have resulted in increased predatory efforts toward smaller seabird species and decreased breeding success in gulls (Regehr andMontevecchi 1997, Stenhouse andMontevecchi 1999). However, declining gull populations could result in less competition over resources and an associated increase in productivity or breeding success (e.g., Bennett et al 2017), which may result in decreased predation on storm-petrels, but these dynamics between predator-prey relationships for conesting seabirds remain poorly known.…”
Section: Influence Of Predation On Nest Site Usementioning
confidence: 99%